2021
DOI: 10.1097/fjc.0000000000000942
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Enhances Foam Cell Lipophagy and Promotes Cholesterol Efflux Through the AMP-Activated Protein Kinase/Mammalian Target of Rapamycin Pathway

Abstract: Foam cells are the main pathological components of atherosclerosis. Therapies reducing foam cell formation can effectively prevent atherosclerotic diseases and cardiovascular events. Beyond lowering plasma cholesterol levels, the pleiotropic functions of statins in atherosclerosis have not been fully elucidated. In the present study, atorvastatin reduced cholesterol content and increased cholesterol efflux from foam cells in a concentration-dependent manner. Atorvastatin (10 μM) inhibited foam cell formation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…This may be related to atorvastatin’s ability to reduce the accumulation of lipids within the neointimal biomimetic hydrogels. This work is consistent with previous studies that have reported that statin can decrease the intracellular lipid contents by stimulating the cholesterol efflux from foam cells [ 71 , 72 ]. As uptake of oxLDL has been shown to induce multiple changes in the cellular phenotype of foam cells [ 73 ], further assessment of the impact of atorvastatin on these genetic and epigenetic responses will be required to assess how atorvastatin has an impact on the thrombogenic properties of the biomimetic hydrogels.…”
Section: Discussionsupporting
confidence: 94%
“…This may be related to atorvastatin’s ability to reduce the accumulation of lipids within the neointimal biomimetic hydrogels. This work is consistent with previous studies that have reported that statin can decrease the intracellular lipid contents by stimulating the cholesterol efflux from foam cells [ 71 , 72 ]. As uptake of oxLDL has been shown to induce multiple changes in the cellular phenotype of foam cells [ 73 ], further assessment of the impact of atorvastatin on these genetic and epigenetic responses will be required to assess how atorvastatin has an impact on the thrombogenic properties of the biomimetic hydrogels.…”
Section: Discussionsupporting
confidence: 94%
“…It was found that atorvastatin enhanced cholesterol efflux and decreased cholesterol content in a dose dependent manner. 17,18 These data suggest that atorvastatin is able to switch macrophages from a pro-inflammatory to an antiinflammatory phenotype, an observation supported by Cheng et al, 14 who noted that atorvastatin was able to modulate the Th1/Th2 response in patients with chronic heart failure through inhibition of Th1 cytokine production. 14 The evaluation of cholesterol efflux is commonly conducted using radioisotope labelled cholesterol that is loaded into cells and quantified.…”
Section: Introductionmentioning
confidence: 75%
“…Moreover, in a study carried out in vitro, rosuvastatin inhibited foam cell formation and stimulated ABCA1 and ABCG1 expression by promoting autophagy in macrophages (Zhang et al, 2021). Similarly, atorvastatin increased cholesterol efflux by promoting foam cell lipophagy (Zheng et al, 2021). Furthermore, pravastatin enhanced cholesterol efflux in chondrocytes (Wu et al, 2022).…”
Section: Statinsmentioning
confidence: 98%